2018
DOI: 10.1186/s41155-018-0094-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the effectiveness of group-based cognitive behavioral therapy and dialectical behavioral therapy in reducing depressive symptoms in Iranian women substance abusers

Abstract: A comparative study of the effectiveness of group-based cognitive behavioral therapy and dialectical behavioral therapy in reducing depressive symptoms in Iranian women substance abusers Sara Sahranavard * and Mohammad Reza Miri AbstractVarious therapeutic approaches have been used to improve depressive symptoms in substance abusers. In a quasiexperimental study with a pretest-posttest design and experimental and control groups, we examined and compared the effectiveness of two group-based treatment strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Participants had, on average, high baseline levels of emotion dysregulation as measured by the DERS (M = 108.87), whereas healthy controls generally score between 63-76 (Becerra et al, 2013;Harrison et al, 2010). Among studies examining the BDI I and II as a measure of depression, both with and without depression as the primary diagnosis, baseline scores showed Two major outliers were detected, (i.e., Sahranavard & Miri, 2018). with z-scores well above 1.96 (z = 3.23 and 2.23, respectively).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants had, on average, high baseline levels of emotion dysregulation as measured by the DERS (M = 108.87), whereas healthy controls generally score between 63-76 (Becerra et al, 2013;Harrison et al, 2010). Among studies examining the BDI I and II as a measure of depression, both with and without depression as the primary diagnosis, baseline scores showed Two major outliers were detected, (i.e., Sahranavard & Miri, 2018). with z-scores well above 1.96 (z = 3.23 and 2.23, respectively).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In order to avoid overestimating the effect of DBT skills groups, we focused on sensitivity analyses in which the two outliers with very large effect sizes (>2 standard deviations) were excluded Sahranavard & Miri, 2018). Notably, both outlier studies were conducted in Iran, indicating potential cultural differences in aspects including mental health, outcome measures, and treatment delivery.…”
Section: Outliers Of Notementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, studies have shown contradictory results about the effectiveness of implementing DBT on various SUD populations (17,18). Furthermore, these pieces of literature have recommended the use of the larger samples, more clear instruments for outcome variables, speci c, and integrated protocols (19).…”
Section: Introductionmentioning
confidence: 99%
“…Research literature shows the e cacy and effectiveness of DBT in various comorbid problems and diseases such as suicide (14), forensic psychiatric patients (15), and irritable bowel syndrome (16). Nevertheless, studies have shown contradictory results about the effectiveness of implementing DBT on various SUD populations (17,18). Furthermore, these pieces of literature have recommended the use of the larger samples, more clear instruments for outcome variables, speci c, and integrated protocols (19).…”
Section: Introductionmentioning
confidence: 99%